Rehabotics: A Comprehensive Rehabilitation Platform for Post-Stroke Spasticity, Incorporating a Soft Glove, a Robotic Exoskeleton Hand and Augmented Reality Serious Games - Pantelis Syringas; Theodore Economopoulos; Ioannis Kouris; Ioannis Kakkos; Georgios Papagiannis; Athanasios Triantafyllou; Nikolaos Tselikas; George K. Matsopoulos; Dimitrios I. Fotiadis (Engineering Proceedings, 2023)
Spasticity following a stroke often leads to severe motor impairments, necessitating comprehensive and personalized rehabilitation protocols. This paper presents Rehabotics, an innovative rehabilitation platform incorporating a multi-component design for the rehabilitation of patients with post-stroke spasticity in the upper limbs. This system incorporates a sensor-equipped soft glove, a robotic exoskeleton hand, and an augmented reality (AR) platform with serious games of varying difficulties for adaptive therapy personalization. The soft glove collects data regarding hand movements and force exertion levels when the patient touches an object. In conjunction with a web camera, this enables real-time physical therapy using AR serious games, thus targeting specific motor skills. The exoskeleton hand, facilitated by servomotors, assists patients in hand movements, specifically aiding in overcoming the challenge of hand opening. The proposed system utilizes the data collected and (in combination with the clinical measurements) provides personalized and refined rehabilitation plans and targeted therapy to the affected hand. A pilot study of Rehabotics was conducted with a sample of 14 stroke patients. This novel system promises to enhance patient engagement and outcomes in post-stroke spasticity rehabilitation by providing a personalized, adaptive, and engaging therapy experience.